Barriers for implementation of intensified hemodialysis: survey results from the International Pediatric Dialysis Network - Thumfart, Julia Angelika; Schaefer, Franz; Schmitt, Claus P. (Pediatric nephrology, 2018)
BackgroundIn patients on conventional hemodialysis (HD), morbidity is high and quality of life is poor. Intensified HD programs have been developed to help overcome these shortcomings, , but very few pediatric dialysis centers have reported the implementation of such a HD program.MethodsAn online survey was sent to all 221 pediatric dialysis centers which participate in the International Pediatric Dialysis Network (IPDN). The aim of the survey was to assess the attitude of pediatric nephrologists towards intensified HD, the penetrance of intensified HD into their clinical practice and barriers to implementation.ResultsOf the 221 pediatric dialysis centers sent the survey, respondents from 61% (134) replied. Among these respondents, 69% acknowledged being aware of the evidence in support of the use of intensified HD, independent of whether intensified HD was offered at their own center, and 50% associated the use of daily nocturnal HD with the best overall patient outcome. In contrast, only 2% of respondents were in favor of conventional HD. Overall, 38% of the respondents stated that at their center intensified HD is prescribed to a subgroup of patients, most commonly in the form of short daily HD sessions. The most important barriers to expansion of intensified HD programs were lack of adequate funding (66%) and shortage of staff (63%), whereas lack of expertise and of motivation were reported infrequently as obstacles (21 and 14%, respectively).ConclusionIntensified HD is considered by many pediatric nephrologists to be the dialysis modality most likely associated with the best patient outcome. The limited use of this treatment approach highlights the importance of defining and successfully addressing the barriers to implementation.